Research progress on multisensory stimulation therapy for pain during retinopathy of prematurity screening - Tao, Chunlan; He, Chuan; Tang, Jinghua; Li, Yongli; Chen, Yuqin (Frontiers in Pediatrics, 2025)
Retinopathy of prematurity (ROP) is a retinal disease characterized by abnormal vascular proliferation, primarily associated with premature delivery and low birth weight. Advances in perinatal and neonatal care have increased survival rates but have also contributed to a rising incidence of ROP, necessitating regular ROP screening. However, the screening procedure, which involves an eyelid speculum and ophthalmoscope, frequently induces pain. Given the potential adverse effects of pharmacological interventions, non-pharmacological pain management is essential. Multisensory stimulation (MSS), integrating auditory, olfactory, gustatory, and tactile stimuli, is recommended by guidelines due to its favorable safety profile and proven analgesic efficacy. This review synthesizes evidence regarding MSS for pain management during ROP screening, focusing on three aspects: operational definitions of MSS [tactile stimuli like non-nutritive sucking (NNS), auditory interventions such as white noise, and gustatory agents including 24% sucrose]. Analgesic mechanisms, particularly sensory pathway competition and endorphin release; and clinical efficacy, with meta-analyses demonstrating superior outcomes of combined interventions (white noise combined with NNS) compared to single-modal approaches. This review aims to provide evidence-based guidance for effectively implementing MSS strategies, ultimately minimizing procedural pain.